The spider family Oecobiidae (Arachnida: Araneae) in Iran, Afghanistan and Turkmenistan - Alireza Zamani; Jan Bosselaers (Museum National d'Histoire Naturelle, 2022)
The taxonomic and faunistic status of the spider family Oecobiidae in Iran, Afghanistan and Turkmenistan is revised. A new species, namely Uroctea gambronica sp. nov. (♂) is described from southern Iran, and the male of U. grossa Roewer, 1960 is described and illustrated for the first time. Additionally, new faunistic data are provided, including the first records of Oecobius putus O. Pickard-Cambridge, 1876 and U. grossa in Afghanistan and Turkmenistan, respectively, and the re-evaluation of previously misidentified and questionable records of this family in the region. The known distribution ranges of all species are mapped for these three countries.